2023
DOI: 10.1021/jacs.3c02556
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Isolable Dearomatized [4 + 2] Cycloadducts from Benzenes, Naphthalenes, and N-Heterocycles Using 1,2-Dihydro-1,2,4,5-tetrazine-3,6-diones as Arenophiles under Visible Light Irradiation

Abstract: We report that the dearomative [4 + 2] cycloaddition between 1,2-dihydro-1,2,4,5-tetrazine-3,6-diones (TETRADs) and benzenes, naphthalenes, or N-heteroaromatic compounds under visible light irradiation affords the corresponding isolable cycloadducts. Several synthetic transformations including transition-metal-catalyzed allylic substitution reactions using the isolated cycloadducts at room temperature or above were demonstrated. Computational studies revealed that the retro-cycloaddition of the benzene–TETRAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…The so obtained cycloadducts 3.6a-c were efficiently functionalized by utilizing different approaches, including palladium-or copper catalyzed allylic substitution processes and non-catalytic hydroboration reaction. 86 The photoinduced arene-alkyne [3+2] cycloaddition of 1alkynylnaphthalen-2-ols (4.1a-c, Scheme 4) under photocatalystfree conditions followed by air mediated oxidation of the obtained hexacycles 4.2a-c was exploited for the efficient and stereoselective preparation of complex three-dimensional hexacyclic architectures 4.3a-c in good yields and complete stereoselectivities. 87 The light-driven [2+2] cycloaddition of olefins has been often exploited as an atom efficient tool to achieve cyclobutane scaffolds.…”
Section: Intermediate Free Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so obtained cycloadducts 3.6a-c were efficiently functionalized by utilizing different approaches, including palladium-or copper catalyzed allylic substitution processes and non-catalytic hydroboration reaction. 86 The photoinduced arene-alkyne [3+2] cycloaddition of 1alkynylnaphthalen-2-ols (4.1a-c, Scheme 4) under photocatalystfree conditions followed by air mediated oxidation of the obtained hexacycles 4.2a-c was exploited for the efficient and stereoselective preparation of complex three-dimensional hexacyclic architectures 4.3a-c in good yields and complete stereoselectivities. 87 The light-driven [2+2] cycloaddition of olefins has been often exploited as an atom efficient tool to achieve cyclobutane scaffolds.…”
Section: Intermediate Free Reactionsmentioning
confidence: 99%
“…The so obtained cycloadducts 3.6a–c were efficiently functionalized by utilizing different approaches, including palladium- or copper catalyzed allylic substitution processes and non-catalytic hydroboration reaction. 86…”
Section: Intermediate Free Reactionsmentioning
confidence: 99%
“…Ikeda et al recently reported the visible-light promoted [4 + 2] cycloaddition between 1,2-dihydro-1,2,4,5-tetrazine-3,6-diones 79 (TETRADs) and aromatics, under white light-irradiation in DCM at À 10 °C, allowing the isolation of the corresponding cycloadducts 80 (Scheme 29). [52] Aromatic compounds substituted with EWG and EDG, naphthalenes, or N-heteroaromatic compounds were exploited to afford a total of 41 products, with yields ranging from 24 to 99 %. Best results were obtained with naphthyl derivatives; when the 2-substituted naphthalene was employed as the starting material, a product derived from two cycloadditions on both rings was observed.…”
Section: Miscellaneous Synthesis Of N-containing Heterocyclesmentioning
confidence: 99%
“…Traditional reactions under UV conditions were synthetically less useful due to often-uncontrollable selectivity 43 – 45 . Notably, a series of enabling dearomative transformations of naphthalenes/benzenes have been reported, which were initiated with visible-light-induced cycloaddition with arenophiles like 4-methyl-1,2,4-triazoline-3,5-dione (MTAD) by Sarlah 46 48 and 1,2-dihydro-1,2,4,5-tetrazine-3,6-diones (TETRADs) by Yoshino and Matsunaga 49 . The groups of Glorius and others achieved a series of photo-induced dearomative [2 + 2] and related cycloadditions of naphthalenes (Fig.…”
Section: Introductionmentioning
confidence: 99%